2013
DOI: 10.4028/www.scientific.net/kem.548.267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Mineralogical and Mortar Components on the Adherence of Some “Granites”

Abstract: Rock plate setting can be performed with metal inserts or by mortar adhesion. For mortar setting, the adhesion bond strength values, as a rule, should be above 1 MPa. In the present work, tests with eight types of “granite” tiles were performed to compare the adherence of five types of mortars. The rocks chosen were: Red Brasilia (syenogranite), Black Indian (migmatite), Green Labrador (charnockite), Black Sao Gabriel (hypersthene diorite), Rose Jacaranda (nebulitic migmatite syenogranite), Fantastic Blue (bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In this study, the specific mortar grout for granite and marble that is marketed worldwide, here called "Commercial Mortar" was compared with other type, here called "Mortar 3" [6] based on a laboratory-prepared mortar for porcelanate [7]. The reason this was chosen is due to the fact that porcelanate and granite have one characteristic in common, very low porosity (< 3%), does not allow anchoring, and the adherence is related to chemical bonds and/or intermolecular forces.…”
Section: B Mortars and Standard Substratementioning
confidence: 99%
“…In this study, the specific mortar grout for granite and marble that is marketed worldwide, here called "Commercial Mortar" was compared with other type, here called "Mortar 3" [6] based on a laboratory-prepared mortar for porcelanate [7]. The reason this was chosen is due to the fact that porcelanate and granite have one characteristic in common, very low porosity (< 3%), does not allow anchoring, and the adherence is related to chemical bonds and/or intermolecular forces.…”
Section: B Mortars and Standard Substratementioning
confidence: 99%
“…Its petrographic and textural characteristics (type, percentage, size, shape, and mineral arrangement, etc.) influence the tensile bond strength of plates set with Nogami et al (2012Nogami et al ( , 2013 showed that adhesion spread was directly proportional to the roughness values Rt (mm), indicating that the larger contact surface provides greater physical interaction (Van der Waals connections) since these rocks have extremely low porosity (B1.01 %). Such characteristic limits the anchoring adhesion (mortar penetration into pores).…”
Section: Tensile Bond Strengthmentioning
confidence: 99%
“…The main objective of this paper is to compare the adherence of an industrial bonding mortar for granite against other laboratory-developed mortars, taking into consideration earlier studies (Nogami et al 2012(Nogami et al , 2013 related to the influence of roughness on the plates and the petrographic characteristics of the stones.…”
Section: Introductionmentioning
confidence: 99%